2017
DOI: 10.1002/trtr.1636
|View full text |Cite
|
Sign up to set email alerts
|

Reading the Past to Inform the Future: 25 Years of The Reading Teacher

Abstract: This analysis examines articles from the past 25 years of The Reading Teacher to better understand the journal's content and trends influencing literacy instruction. A research team coded and analyzed the frequency of topics and grade levels targeted, then compared results with those of a similar analysis published in 1992. The Web of Science provided current information about trends in authorship and the popularity of highly cited and frequently accessed articles. This report shares various metrics, insights,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…On the other hand, researchers tend to cite high‐quality papers and indicative papers that are useful for their own research (Mohr et al , ). A high citation count is an indication of high impact on the research field, and reveals the recognition of research advancement (Fu & Ho, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, researchers tend to cite high‐quality papers and indicative papers that are useful for their own research (Mohr et al , ). A high citation count is an indication of high impact on the research field, and reveals the recognition of research advancement (Fu & Ho, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study relates to other content analyses of professional literacy journals (Dillon et al, 1992;Mohr et al, 2007;Pearson, 1992) in which manuscripts appearing in literacy journals were examined for topics and trends in literacy education. In those previous content analyses, such as Dillon et al (1992), the researchers found that the most frequently appearing topics were those using empirical data to support particular methods of teaching, innovative instructional strategies, assessment methods and manuscripts about children's literature.…”
Section: Discussionmentioning
confidence: 99%
“…Pearson's (1992) study found that readiness, emergent, beginning reading, and disability were the most frequently occurring topics discussed in his content review. Mohr et al (2007) found that instructional strategies, children's literature, and writing were the most frequent topics appearing in her 25year review of The Reading Teacher.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the journal impact factor originated in the late 1950s and early 1960s as a measure to gauge the frequency of citations particular journals receive in articles (Blessinger & Hrycaj, 2010). Researchers tend to select high-quality, indicative, and peer-reviewed papers when reading and citing literature, typically associated with a high citation count (Lai, 2020;Mohr et…”
Section: Introductionmentioning
confidence: 99%